Violation of The Principle of Equality Before the Law in The Case of Ilaria Salis - Gelora, Mahardika Ahmad (Uti Possidetis: Journal of International Law, 2025)
Background: The principles of equality before the law and legal certainty are fundamental tenets of a rule-of-law state. Although the European Union (EU) operates under a sui generis legal framework, it is still expected to uphold these core legal principles. The case of Ilaria Salis, an Italian activist granted immunity despite her involvement in a criminal proceeding, raises concerns about the status of EU law within the international legal order. Methodology: Through a normative juridical analysis, this study examines the legal implications of granting immunity in the context of EU law. Objectives: To assess whether the immunity granted in the Ilaria Salis case is consistent with the fundamental legal principles of equality before the law and legal certainty, as recognized by EU legal instruments and jurisprudence. Findings: The study finds that the granting of immunity in this case led to a violation of both principles under EU legal standards, highlighting potential inconsistencies in the application of EU law. Originality/Novelty: This research addresses a contemporary legal dilemma by critically evaluating how the application of immunity in a high-profile case may undermine the foundational legal principles of the EU, thus questioning the coherence of EU law within the international legal framework.